Controllable synthesis of organic-inorganic hybrid halide perovskite quantum dots for quasi-solid-state solar cells. (20th August 2018) - Duan, Jialong; Zhao, Yuanyuan; He, Benlin; Jiao, Zhengbo; Tang, Qunwei
Abstract: Photovoltaics are regarded as the promising solution to resolve energy and environmental problems owing to their high power conversion efficiency and zero emissions. However, the narrow-spectra absorption range and serious recombination reactions at electrode/electrolyte interfaces are two major drawbacks for high-performance solar cells. Herein, a new way of synthesizing organic-inorganic hybrid CH3 NH3 PbX3 (X = Cl, Br or I) perovskite quantum dots (PQDs) is demonstrated by dropping perovskite precursor solution into anhydrous toluene. After a systematic study, the results demonstrate that the energy levels of PQDs can be tuned through optimizing the stoichiometric ratio of halide ions, showing good optical properties for photovoltaic applications. A quasi-solid-state sensitized solar cell with configuration of FTO/ m -TiO2 /PQDs/dye/long persistence phosphor/gel electrolyte/Pt/FTO is fabricated, yielding an impressive power conversion efficiency as high as 7.91%, which is higher than 7.26% for referenced device free of PQDs. The improved performances are mainly attributed to the increased light absorption as well as reduced recombination upon the incorporation of PQDs and long persistence phosphor into devices. Graphical abstract: Image 1 Highlights: Organic-inorganic hybrid perovskite quantum dots are fabricated. Energy levels of PQDs are tuned by changing the stoichiometric ratio of halide ions. PQDs are inserted into the quasi-solid-state solar cells to boost charge extraction. A power conversion efficiency as high as 7.91% is achieved.